2018
DOI: 10.1007/s00025-018-0939-x
|View full text |Cite
|
Sign up to set email alerts
|

Almost Para-Hermitian and Almost Paracontact Metric Structures Induced by Natural Riemann Extensions

Abstract: In this paper we consider a manifold (M, ∇) with a symmetric linear connection ∇ which induces on the cotangent bundle T * M of M a semi-Riemannian metric g with a neutral signature. The metric g is called natural Riemann extension and it is a generalization (made by M. Sekizawa and O. Kowalski) of the Riemann extension, introduced by E. K. Patterson and A. G. Walker (1952). We construct two almost para-Hermitian structures on (T * M, g) which are almost para-Kähler or para-Kähler and prove that the defined al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…In [1] it is shown that, for any t ∈ R * , the restriction of the natural Riemann extension g to H t , denoted by g, gives rise to an almost paracontact structure (ϕ, ξ, η, g) on H t with (6.6)…”
Section: By Applying the Equivalencementioning
confidence: 99%
See 2 more Smart Citations
“…In [1] it is shown that, for any t ∈ R * , the restriction of the natural Riemann extension g to H t , denoted by g, gives rise to an almost paracontact structure (ϕ, ξ, η, g) on H t with (6.6)…”
Section: By Applying the Equivalencementioning
confidence: 99%
“…More precisely, the second aim here is to study geodesics and magnetic curves on a family of level surfaces of the phase space, whose construction is recalled from [2]. In [1], these hypersurfaces are endowed with almost paracontact structures. Paracontact geometry appears in [8] as a counterpart of contact geometry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C.-L. Bejan [1,2] classified almost para-Hermitian spaces and found some examples of spaces with hyperbolic structures. Recently, C.-L. Bejan and G. Nakova [3] studied almost para-Hermitian and almost paracontact metric structures induced by natural Riemann extensions. Some interesting results concerning para-Kähler-like statistical submersions were obtained by G. E. Vîlcu [4].…”
Section: Introductionmentioning
confidence: 99%
“…As a particular situation, when a = 1 and b = 0, we get the Riemannian extension. For further references relation to the natural Riemann extension, see[5][6][7]13].…”
mentioning
confidence: 99%